Upaya Memahami Mindfullness untuk Mendorong Rasa Percaya Diri Siswa Muslimeen Suksa School, Hatyai, Thailand - Hardani Widhiastuti; Faisal Yusuf; Andi Nurcahyo; Rusmalia Dewi; Adul Meatam (Jurnal Nusantara Berbakti, 2024)
This international community service was conducted at Muslimeen Suksa School, Hatyai, Thailand. This PKM was conducted with the aim of providing training with the theme of Mindfullness to increase students' self-confidence. The problem that often occurs is that to motivate students' self-confidence, there is no specific curriculum that supports it. Moreover, students equivalent to high school prioritize emotional souls that are sometimes not accompanied by positive thinking, which has an impact on suboptimal self-confidence. Age is one of the considerations, considering that high school age is an age that prioritizes spontaneity or what is desired. Sometimes ideals have not been described by them. The method of this activity is in the form of training by distributing pretest and posttest answers to show participants' understanding before and after the material is given about Mindfullness, which is expected to increase students' self-confidence with the method being training that takes almost 3 hours, which is attended by around 75 students and 5 teachers and 1 principal. The results obtained in the form of descriptive qualitative by explaining and describing the conditions of participants who participated in this activity happily and enthusiastically, considering that this was the first activity to be followed and carried out by higher education institutions from Indonesia. The end of this activity is closed with relaxation